2019
DOI: 10.2139/ssrn.3399742
|View full text |Cite
|
Sign up to set email alerts
|

Urns Filled with Bitcoins: New Perspectives on Proof-of-Work Mining

Abstract: The probability of a miner finding a valid block in the bitcoin blockchain is assumed to follow the Poisson distribution. However, simple, descriptive, statistical analysis reveals that blocks requiring a lot of time to find-long blocks-are won only by miners with a relatively higher hash power per second. This suggests that relatively bigger miners might have an advantage with regard to winning long blocks, which can be understood as a sort of "within block learning". Modelling the bitcoin mining problem as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our estimates suggest that negative network externality dominates positive network externality. Our results are in line with those of Parra-Moyano, Reich, and Schmedders (2019), who found that the probability of winning a mining contest increases with the miner size. This motivates miners to join mining pools to increase their probability of winning the mining contest and receiving the reward.…”
Section: Competition and Network Externalitiessupporting
confidence: 92%
See 2 more Smart Citations
“…Our estimates suggest that negative network externality dominates positive network externality. Our results are in line with those of Parra-Moyano, Reich, and Schmedders (2019), who found that the probability of winning a mining contest increases with the miner size. This motivates miners to join mining pools to increase their probability of winning the mining contest and receiving the reward.…”
Section: Competition and Network Externalitiessupporting
confidence: 92%
“…Cocco and Marchesi 2016; Thum 2018; Schilling and Uhlig 2019). However, Parra-Moyano, Reich and Schmedders (2019) show that the probability of relatively bigger miners winning the mining contest is higher than that of relatively smaller miners because there is a "learning" effect when mining a particular block with larger mining computers learning faster than smaller mining computers. To account for the learning by mining, we assume the following transformation of the probability for a miner winning a block: ), where 𝛾 is a transformation parameter (with 0 < 𝛾 ≤ 0), which implies that the ratio of odds between big and small miners (mining computers) of winning a block increases with the miners' size, m it , while keeping the ratio of miner' size between miners fixed.…”
Section: 𝑛 𝑡 𝑗≠𝑖mentioning
confidence: 94%
See 1 more Smart Citation
“…PoW is a memoryless process, i.e., for each miner the probability of solving the puzzle in a certain time slot is independent of how long he/she has been working on it. This has two consequences [29]. First, the time between two consecutive block consolidations is independent and exponentially distributed, since the exponential distribution is the only nonnegative continuous distribution that satisfies the memoryless property.…”
Section: A Proof Of Work (Pow)mentioning
confidence: 99%